Extreme Drought Conditions Can Drastically Change Age Structure of a Plant Population: Case Study of Jacobaea paludosa subsp. Lanata (Family: Asteraceae) in The Republic of Mordovia (Russia) - Khapugin, Anatoliy A.; Kunaeva, Elena N.; Silaeva, Tatyana B. (Journal of the Bombay Natural History Society (JBNHS), 2018)
No Abstract.